PENGARUH FASILITAS DAN KUALITAS PELAYANAN TERHADAP KEPUASAN PENUMPANG PENGGUNA TRANS BATAM DIKORIDOR SEKUPANG-JODOH - Melinda Putri, Ratna; Purba, Tiurniari (LPPM Universitas Putera Batam, 2021)
One of the public transportation in Batam City, namely the Trans Batam Bus. The Trans Batam Bus is a public transportation presented by the Batam City government to the public. In an effort to create passenger satisfaction. Facilities and survice quality by maintaining the value of passenger satisfaction. Determined the effect of facilities and service quality on the satisfaction of passengers using Trans Batam in the Sekupang-Jodoh corridor was the purpose of the sudy. A quantitative method was used to solve the problems in which questionnaires are distributed as instruments in data collection. The sample technique used to collect data in this study is sampling using a probability sampling technique or called simple random sampling. With a total of 100 respondents using the Trans Batam Bus. The results of the research that were tested using SPSS version 25 showed that passenger satisfaction was influenced by facilities and service quality with an R Square value of 0.843 or 84,3%. The study showed the results that the variabel facilities and service quality give a positive and significant effect on passenger satisfaction. Ketwords: Facilities; Passenger Satisfaction; service Quality.